Rehearsing experts and ‘inperts’: Crossing transnational housing narratives in West Africa - Pacheco, M. (Planning Perspectives, 2022)
In the early days of the United Nations, the main form of aid in the field of housing took the shape of technical assistance. Although the pool of specialists was almost coincident with those from colonial networks, the ambitions and limitations of international, non-governmental and neutral cooperation implied a reconceptualisation of the world division inherited from the colonial period and its replacement by a new paradigm of ‘development’. This manifested itself right from the start in the redefinition of the modus operandi of the expert and in the production of a particular form of knowledge that challenged the previous expertise, influencing narratives on the built environment around the world. This paper examines the 1954 United Nations Housing Mission to the Gold Coast and its outcomes, along with the formative example of the previous 1950 mission to prepare the UN Expanded Programme of Technical Assistance. The case study provides an insight into the relationship between the idealization of international cooperation and that of the expert in the field of housing. At the same time, the emphasis on research and education, and the subsequent foundation of a new school, offers a starting point for a critical analysis of its counterpart, the ‘inpert’.